GAMBARAN PERILAKU MASYARAKAT TENTANG ISOLASI MANDIRI CORONAVIRUS DISEASE (COVID-19) DI WILAYAH KERJA PUSKESMAS PAUH TAHUN 2021 - Devin Mahendika; Multazam Fahreza Chandra; Astri Dwi Andini; Mai Ismil Husni Tasyriqiyyah; Naila Widanti; Sylfia Mustika; Ida Rahmah Burhan; Ema Julita (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2022)
Introduction: Coronavirus Disease-19 (COVID-19) was a disease caused by SARS-CoV-2. The positivity rate for COVID-19 at the Pauh Health Center until August 2021 reached 34.95%. Most of the people lived in Pauh who have been confirmed COVID-19 were self-isolating. Method: This study used a political and logical approach with descriptive and cross-sectional design. The research was conducted from August – September 2021 in Cupak Tangah, South Limau Manis, and Koto Luar. The research data was obtained by filling out the respondent's questionnaire and guided interview. Result: The problem found using the Hanlon method was the high positivity rate of COVID-19 at the Pauh Health Center. This was due to several factors, such as the lack of public knowledge about COVID-19 and self-isolation, lack of awareness in implementing health protocols, lack of concern and negative stigma towards people who are confirmed to have COVID-19, lack of strict supervision of health protocols by cross-sectors, and obstacles in purchasing. Standard Personal Protective Equipment (PPE). Discussion: Health promotion with modules was chosen based on the demographic and geographical conditions of the Pauh with the aim of providing an understanding of self-isolation. Other activities carried out are socialization and evaluation in the form of pre and post tests targeting the community, health workers, and officials in the Pauh. Conclusion: The solution to the high COVID-19 positivity rate in the Pauh Health Center work area was to form an independent isolation module using the Plan, Do, Check, and Action (PDCA) flow, making this module can be an outcome in helping to improve people's behavior and educating the public to behave well according to the rules. Keywords: COVID-19, module, primary health care, self-isolation